If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6000 = x(x + -40) Reorder the terms: 6000 = x(-40 + x) 6000 = (-40 * x + x * x) 6000 = (-40x + x2) Solving 6000 = -40x + x2 Solving for variable 'x'. Reorder the terms: 6000 + 40x + -1x2 = -40x + 40x + x2 + -1x2 Combine like terms: -40x + 40x = 0 6000 + 40x + -1x2 = 0 + x2 + -1x2 6000 + 40x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 6000 + 40x + -1x2 = 0 Factor a trinomial. (100 + -1x)(60 + x) = 0Subproblem 1
Set the factor '(100 + -1x)' equal to zero and attempt to solve: Simplifying 100 + -1x = 0 Solving 100 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-100' to each side of the equation. 100 + -100 + -1x = 0 + -100 Combine like terms: 100 + -100 = 0 0 + -1x = 0 + -100 -1x = 0 + -100 Combine like terms: 0 + -100 = -100 -1x = -100 Divide each side by '-1'. x = 100 Simplifying x = 100Subproblem 2
Set the factor '(60 + x)' equal to zero and attempt to solve: Simplifying 60 + x = 0 Solving 60 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + x = 0 + -60 x = 0 + -60 Combine like terms: 0 + -60 = -60 x = -60 Simplifying x = -60Solution
x = {100, -60}
| 5y+4=4y+50 | | F=2KG+2KH | | 7(5x-8)-4(8x+3)=-68 | | 2x-4-3x+30=6 | | 5y+40=5y+40 | | 4x^2-6.25=0 | | f(x)=x^2+40 | | (5x+2)(6x-10)(x+20)=180 | | 5v-8=-53 | | 200-(-400)= | | J(u-w)=t | | X^2-14x-234=0 | | 6v(4v-8)= | | 70=.28*x | | 49b^2=256 | | 3x^2+10x+8=-2 | | 4[x-5]=-3[x-5] | | 3a+12b+15= | | 9[7-(7x-9)]+6x=0 | | -2x+24=0 | | 12x+-9+62+-3x+16x+2=180 | | 4x*2=49 | | 8(x-3)+5=8x+7 | | 3(2z-6)-4(3z+1)=5-2(2+1) | | 6x+3y+9x+y= | | 3n+4=8n-1 | | 4(2w+3)+2(3+w)= | | 4(w-6)=3(a+1) | | 7x+13=2x+8 | | -21+7y=9x | | 58-2+7=8x | | 3a+34b= |